Molecular phylogeny and species delimitation of the genus Schizodon (Characiformes, Anostomidae) - Ramirez, Jorge L. (2020)
The genus Schizodon is part of a group of headstanders and relatives (Family Anostomidae) that are widespread and ecologically important fishes in South American rivers. Schizodon includes 15 nominal species but their taxonomy has been challenging due to paucity of decisive characters to diagnose species. We present new molecular data to assess species boundaries or molecular operational taxonomic units (MOTUs), and to infer phylogenetic relationships among species. Evidence from two mitochondrial and three nuclear genes was used in these analyses. Mitochondrial DNA data for 112 specimens (from 11 nominal species) supported 13 consensus MOTUs, six of which matched valid nominal species (Schizodon borellii, S. fasciatus, S. intermedius, S. isognathus, S. knerii and S. scotorhabdotus). The nominal species Schizodon vittatus, S. nasutus, and S. dissimilis were subdivided into two MOTUs each, revealing either cryptic species or strong population structuring. In contrast, S. platae and S. jacuiensis constituted a single MOTU, indicating a possible case of synonymy. Our phylogenetic analysis subdivided the genus Schizodon into two large clades that are compatible with observed color patterns and biogeographic distribution. The first Glade includes species with three to four conspicuous dark vertical bars on the flanks that originated in the Amazonas region (S. borellii, S. dissimilis, S. intermedius, S. fasciatus, S. scotorhabdotus, S. vittatus, and a cryptic species, Schizodon aff. vittatus). The second Glade includes species with a conspicuous dark caudal blotch on the caudal peduncle, with vertical bars absent or inconspicuous, with a biogeographic origin in the La Plata drainage (S. isognathus, S. jacuiensis, S. knerii, S. nasutus and S. platae). Our results reinforce the importance of using molecular analyses to accelerate the study of diversity, particularly in groups with a wide distribution, few variable meristic characters, and high morphological plasticity, which may hide still unknown or underestimated diversity.